Psychological mechanisms and interventions directed at vaccination attitudes - Ann, Sidonie; Baumann, Oliver (Frontiers in Sociology, 2023)
Attitudes about vaccination impact not only the individual but also society. Therefore, understanding the underlying psychological processes of those who disagree with vaccination is critical in creating compassion through understanding and change through promoting autonomy. The current review aimed to fill a gap in the literature, outlining the state of the recent research on vaccination attitudes, specifically on the underlying mechanisms driving anti-vaccination movements and individuals' thoughts and behaviours. In addition, we aimed to evaluate current research on the effectiveness of interventions targeting these mechanisms. Overall, results indicated that those declining vaccines had beliefs related to distrust in the scientific community and pharmaceutical companies and moral preferences for purity and liberty. Additionally, our review identified the potential for utilising motivational interviewing techniques as an intervention. This literature review provides a platform for further research and enhances the current understanding of vaccination attitudes.